Efforts to Stimulate Entrepreneurship Character for Early Childhood through Innovative Learning Methods Based on Science, Technology, Engineering, Art, and Math (STEAM) - Nandang Rukanda (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
This study aims to examine innovative learning methods based on Science, Technology, Engineering, Art, and Math (STEAM) to stimulate the formation of mental entrepreneurship for young children so that in the future they become independent entrepreneurs. This study uses several theoretical studies that are used as a basis, namely the theory of out of school education, critical pedagogy, and entrepreneurship. The qualitative approach with the case study method is used by the writer as a research approach. The results showed that the application of STEAM learning methods in early childhood students can stimulate the formation of their entrepreneurial spirit for their future.Keywords: Out-of-School Education; Critical Pedagogy; Entrepreneurship. AbstrakPenelitian ini bertujuan untuk mengkaji metode pembelajaran inovatif berbasis Science, Technology, Enginering, Art, dan Math (STEAM) dalam rangka menstimulasi pembentukan mental entrepeneur bagi anak usia dini supaya di masa depan menjadi wirausaha mandiri. Penelitian ini menggunakan beberapa kajian teoretis yang dijadikan landasan, yakni teori pendidikan luar sekolah, pedagogi kritis, dan kewirausahaan. Pendekatan kualitatif dengan metode studi kasus digunakan penulis sebagai pendekatan penelitian. Hasil penelitian memperlihatkan bahwa penerapan metode pembelajaran STEAM pada peserta didik anak usia dini dapat menstimulasi pembentukan jiwa wirausaha mereka untuk untuk masa depannya.Kata Kunci: Pendidikan Luar Sekolah; Pedagogi Kritis; Kewirausahaan.